The Local Image between Critical Vision and Reality of the Seasoned Poet (Lamiat Rabeea Ben Maqroom Al Dadhbi) - Sahal, Dailam Kahdim; Alwan, Malath Natiq (International Journal of Psychosocial Rehabilitation, 2020)
The Local image is the result of imagination that helps the poet on the formatting of the external reality anew composition in the poetic text, making stock of his imagination to the details of daily life and its preset scenes within the framework of emotional space and time, convenient splintering poetic images filled with passion, motivating the recipient to interact with the poet’s commercial and his life issues, which he colored in his imagination based on emotional or visual recollection, or any recall based on one of his established senses, to be an innovative coloring that presets an image of external reality its content are the poets daily experiences and life elements, to bring forth an innovative new local birth that infuses spiritual meanings that affect the soul, and confirmed the interesting admiration of the poetic text maker. So simulating the temporal moment with spatial– the moment of the daily human existence of the poet- fantastically redraw it again with a distinctive creative coloring that makes the local image a polarization of my emotional drive within the text.